A prospective randomized comparative study of laparoscopic appendicectomy versus open appendicestomy in Hospital Universiti Sains Malaysia - Prakash, Bhoma Anand (2006)
Background: Since the demonstration of laparoscopic appendicectomy by K. Semm in 1983, it is performed worldwide though criticized by many. Open appendicectomy is a brief procedure but is definitely associated with morbidity and can cause difficulty in uncertain diagnosis. Laparoscopic appendicectomy has been a standard surgical procedure performed in Hospital Universiti Sains Malaysia, but a prospective randomized study comparing various parameters in between LA and OA has not been done before. Objectives: To compare various surgical times, complications and outcomes in between LA and OA in HUSM. Design: Prospective randomized comparative study. Results: This study was conducted in Hospital Universiti Sains Malaysia from February 2006 till November 2006. Total of 97 patients were randomized in the study. Amongst them, 53 patients underwent open appendicectomy (OA) and 44 patients underwent laparoscopic appendicectomy (LA). In the study, 54.6% patients were males and 45.4% were females (P = 0.2). The median age in LA and OA groups was 18 and 20 years respectively. The mean Body Mass Index (BMI) in both groups was same. (22kglm2) Patients in LA group had to wait longer for appendicectomy compared with OA groupand it was 22.2 hours versus 15.8 hours (P = 0.04). The operating time for laparoscopic appendicectomy group as well as for open appendicectomy group was similar (70.2 minutes). Patients in LA group tolerated normal diet significantly earlier (36.6 hours versus 55.4 hours, P = 0.05) and were discharged earlier compared to OA group (2.4 days versus 3.6 days, P=0.2). Eight patients in the laparoscopic group were converted to OA, intra-operatively (18.1 %). Acute appendicitis was the commonest intra-operative finding (72.2%) followed by perforated appendicitis (20.6%). Wound infection rate in OA group was 7.5% compared to 2.8% in LA group. The overall negative appendicectomy rate was 3.1% in the study. Conclusion: The results of this prospective randomized comparative study disapproves the concept that laparoscopic appendicectomy is a prolonged procedure, when compared to open appendicectomy. So the perception that laparoscopic appendicectomy is a prolonged procedure should be avoided. There is early return of bowel function, shorter post operative hospital stay, less pain and lower wound infection rate after laparoscopic appendicectomy when compared to open appendicectomy. Perforated and gangrenous appendicitis can also be handled by laparoscopic appendicectomy safely and are not the contraindications for laparoscopic appendicectomy. Diagnostic laparoscopy should be considered among females in reproductive age group with uncertain diagnosis.